2019
DOI: 10.1016/j.cognition.2019.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Does the implicit outcomes expectancies shape learning and memory processes?

Abstract: Does the explicit or implicit knowledge about the consequences of our choices shape learning and memory processes? This seems to be the case according to previous studies demonstrating improvements in learning and retention of symbolic relations and in visuospatial recognition memory when each correct choice is reinforced with its own unique and explicit outcome (the differential outcomes procedure, DOP). In the present study, we aim to extend these findings by exploring the impact of the DOP under conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Furthermore, in both cases, the activation of the angular gyrus of the posterior parietal cortex was observed, indicating its involvement in prospective memory. A recent study has also demonstrated that, as the two-memory system model suggests, this prospective memory is largely implicit [51]. In fact, participants showed a better visual recognition memory when the DOP was applied regardless of whether the outcomes or the sample stimuli were presented under subliminal (non-conscious) or supraliminal (conscious) conditions.…”
Section: Plos Onementioning
confidence: 95%
“…Furthermore, in both cases, the activation of the angular gyrus of the posterior parietal cortex was observed, indicating its involvement in prospective memory. A recent study has also demonstrated that, as the two-memory system model suggests, this prospective memory is largely implicit [51]. In fact, participants showed a better visual recognition memory when the DOP was applied regardless of whether the outcomes or the sample stimuli were presented under subliminal (non-conscious) or supraliminal (conscious) conditions.…”
Section: Plos Onementioning
confidence: 95%
“…Mental rotation was assessed with a task designed using the E‐Prime 2.0 software (Psychology Software Tools, 2007), adapted from Carmona, Marí‐Beffa and Estévez (2019). The stimuli were displayed over a black background and consisted in 436‐pixel‐diameter circles with a white outline that was segmented into 16 equal portions (two of them colored white) by eight radial lines, which were also white (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…2 and Fig. 3), designed with AutoCAD software (Autodesk Software, 2010) by Carmona et al (2019b). The sample stimuli were white geometrical shapes designed for the occasion.…”
Section: Settings and Materialsmentioning
confidence: 99%
“…In addition to revealing the usefulness of the DOP, another major goal has been to identify the circumstances under which the advantage of the DOP over NOP emerges. For example, some studies have reported a modulation of the DOE by task di culty (e.g., Estévez, Vivas, Alonso, Marí-Beffa, Fuentes, & Overmier, 2007; Plaza et al, 2011), and other studies have shown that it is not necessary to have conscious experience of the stimuli involved for the bene t of DOP to occur (e.g., Carmona et al, 2019b; Carmona, Ortells, Fuentes, Kiefer, & Estévez, 2020). However, to our knowledge, no studies have addressed how participants select the relevant stimulus in the presence of irrelevant stimuli in the DOP context.…”
Section: Introductionmentioning
confidence: 99%